The continual search for ideal biomarkers for mesothelioma: The hurdles - Brims, Fraser; Gary Lee, Y.; Creaney, J. (Pioneer Bioscience Publishing Company, 2013)
Malignant pleural mesothelioma (MPM) is an aggressive tumour predominately caused by exposure to asbestos. Asbestos consumption continues to increase worldwide, particularly among developing nations in Asia. Although actual data on mesothelioma incident rates are unavailable from several of the world’s largest asbestos consuming nations including Russia, China and India (1), rates are predicted to surge in Asia reflecting the increased use of asbestos (2). Presently one person dies every four hours from mesothelioma in the United Kingdom.